Information and Communication Technology (ICT) in the context of Rural Women Empowerment - Sahu, Gaurav; Anant, Manharan; Tiwari, Sushma (The journal of contemporary issues in business and government, 2023)
The advancements in technology have revolutionized the world, with information and communication technology (ICT) emerging as a significant catalyst for change. ICT has not only bridged geographical distances within villages, towns, and countries but has also connected people worldwide. This research paper focuses on the transformative power of ICT in empowering rural women and its role in overcoming various challenges. By highlighting the importance of women's participation in information technology, it aims to demonstrate how ICT facilitates access to resources, services, and opportunities for women, ultimately leading to the creation of an empowered society. Through an examination of the impact of ICT on women's empowerment, this study sheds light on the ways in which technology acts as a driving force for positive change and equality.